PERKEMBANGAN PRODUK DOMESTIK REGIONAL BRUTO PER KAPITA 30 PROVINSI DI INDONESIA PERIODE 1993-2003: PENDEKATAN DISPARITAS REGIONAL DAN KONVERGENSI - Diah Prasasti (Journal of Indonesian Economy and Business (JIEB), 2006)
This research is aimed to identify regional disparity of per capita GRDP at 1993 constant price of 30 provinces in Indonesia over the period 1993-2003. It attempts to address one fundamental question: to what extent is the economic performance of these provinces converging or diverging? It used secondary and establishment data BPS (Indonesia’s Bureau Statistic). The methods of analysis are Williamson Index, OLS (Ordinary Least Square) regression using panel data, and convergence analysis. The research showed that the regional disparity using Williamson Index tend to decrease towards the equalization. OLS regression analysis showed that key factors that affect significantly increasing speed of convergence the growth of per capita GRDP are initial income, human capital characteristic, dummy resources, and dummy crisis. Convergence analysis indicated that Indonesia should growth at least 4.5 percent per year for its convergence growth. This result is consistent with Williamson index which shows that the dispersion of per capita GRDP reduced over time. This research has a same conclusion with Lall & Yilmaz (2000), about catching-up hypothesis, in which “poor” provinces, as measured by low per capita GRDP, displayed faster growth rates in per capita GRDP than “rich” provinces with higher per capita GRDP.